2021
DOI: 10.1111/fwb.13805
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and spatial connectivity drive patterns in freshwater macroinvertebrate diversity across the Arctic

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Temperature and spatial connectivity were identified in the special issue as two main factors that constrain Arctic freshwater α diversity (see Laske et al., 2022; Lento, Culp et al., 2022; Schartau et al., 2022), and our broad‐scale multi‐organism assessment of average standardised diversity corroborated these findings (Figure 2). Low diversity was observed in cold regions at high latitudes and high elevations and where there are barriers to dispersal (on islands and around mountain ranges).…”
Section: Alpha Diversitysupporting
confidence: 77%
See 2 more Smart Citations
“…Temperature and spatial connectivity were identified in the special issue as two main factors that constrain Arctic freshwater α diversity (see Laske et al., 2022; Lento, Culp et al., 2022; Schartau et al., 2022), and our broad‐scale multi‐organism assessment of average standardised diversity corroborated these findings (Figure 2). Low diversity was observed in cold regions at high latitudes and high elevations and where there are barriers to dispersal (on islands and around mountain ranges).…”
Section: Alpha Diversitysupporting
confidence: 77%
“…In circumpolar assessments, α diversity was lowest at the highest latitudes for benthic diatoms (Kahlert et al., 2022), plankton (Schartau et al., 2022), benthic macroinvertebrates (Lento, Culp et al., 2022), and fish (Laske et al., 2022), and showed general declines with increasing latitudes. This latitudinal decline was strongest and most consistent for benthic macroinvertebrates, both at circumpolar and regional scales (Lento, Culp et al., 2022; Lento, Laske et al., 2022). Hotspots for biodiversity varied among taxonomic groups, but commonly included Fennoscandia, low‐latitude and low‐altitude regions of Canada, and coastal regions of Alaska.…”
Section: Alpha Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although some samples from Norway were collected much earlier than samples from Finland or Sweden, their inclusion was necessary to maximise the spatial coverage of the data. Broad‐scale river monitoring data from across the circumpolar regions typically include 2–3 decades of surveying due to the high cost and difficulties involved in accessing remote locations, and such samples have been analysed in spatial contexts to maximise the number of regions that can be considered (Izaguirre et al., 2016; Lento et al., 2022). In addition, Huttunen et al (2012) demonstrated the temporal stability of benthic macroinvertebrate assemblages across northern Fennoscandian streams (66–67°N) among years, indicating that data could be merged across years.…”
Section: Methodsmentioning
confidence: 99%
“…Lento et al. (2022) evaluate α and β diversity of benthic macroinvertebrates in >1,500 lakes and rivers across the circumpolar region. Rarified α diversity of benthic macroinvertebrates declines with increasing latitude in both lakes and rivers, although more strongly across mainland regions than islands.…”
Section: Assessing Freshwater Biodiversity Across the Circumpolar Regionmentioning
confidence: 99%